(Me4N)2SO4•4SnPh3NCS AND (Me2N)2CO•4SnPh3Cl - SYNTHESIS AND SPECTROSCOPIC STUDIES - Libasse Diop; Kochikpa A. Y. Okio (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry, 2010)
Two tetranuclear SnPh3 residue containing adducts have been synthesized and characterized by infrared and Mössbauer spectroscopies. The structure are both discrete, the sulphate anion and the tetramethyl NN’ urea (TMU) acting as tetracoordinating ligands, the environment around the tin IV centres being trans trigonal bipyramidal.